Municipal Water Project Managers: A Hard Road Gets Harder. Issue 9 (3rd September 2019) - Kerr, Donald
Key Takeaways: Hiring a consultant for a water project is a responsibility for which municipal officials are not always well trained and prepared. The skills and authority exercised by consultants have been compromised by limited training, certain business models, legislation, and a city's bottom line. Consulting engineers could benefit from adding political know‐how to their toolbox of expertise.